Notes on the specific identity of Synotis damiaoshanica (Compositae, Senecioneae), with clarification of the confusing identities of S. guizhouensis and S. sinica - Fan, Yu; Wang, Long-Yuan; Zhang, Rui; Tang, Ming (Phytotaxa, 2022)
Careful examination of herbarium specimens and observation of living plants demonstrated that Synotis damiaoshanica is conspecific with S. guizhouensis and should be merged. Morphological differences of S. guizhouensis and its two most close allies, i.e. S. austroyunnanensis and S. sinica are discussed. Color plates of S. guizhouensis, S. damiaoshanica and S. austroyunnanensis are illustrated, a distribution map and a key to the three species are provided.